Effects of free-stream turbulence on wind loads on a full-scale large cooling tower. Issue 10 (July 2018) - Cheng, XX; Dong, J; Peng, Y; Zhao, L; Ge, YJ
The high variability in turbulence is a significant feature of the realistic atmospheric boundary layer winds which might have strong effects on wind loads on structures submerged in atmospheric boundary layer. This article has been devoted to this matter of science which is of practical importance to wind-engineering design and research. First, the variation of the turbulence intensity of the atmospheric boundary layer flow has been studied using theoretical calculations and meteorological wind measurements. Second, the effects of free-stream turbulence on wind loads on circular cylindrical structures have been revealed at high Reynolds number and equivalent conditions based on field measurements and wind tunnel model tests for wind effects on a large cooling tower. Through these works, it is found that the turbulence intensity for the measured atmospheric boundary layer winds is highly variable due to the significant effect of the mean wind speed, which is not well represented by the traditional empirical formulae. Besides, the free-stream turbulence significantly influences the dynamic characteristics of wind effects on the cooling tower in most cases, and the wind effects for a flow field of high turbulence intensity are generally more unfavorable than those for a flow field of low turbulence intensity.